Circular Product Design. A Multiple Loops Life Cycle Design Approach for the Circular Economy. (28th July 2017) - Mestre, Ana; Cooper, Tim
Abstract: The circular economy is a high priority subject of discussion in the current political and academic contexts; however, practical approaches in relevant disciplines like design are in need of development. This article proposes a conceptual framework for circular product design, based on four multiple loops strategies: (I) design to slow the loops, (II) design to close the loops, (III) design for bio-inspired loops, and (IV) design for bio-based loops. Recent literature, notably on life cycle design strategies, the circular economy conceptual model and the European Commission's Circular Economy Package, is reviewed and product design cases illustrating each of the proposed are analysed. The article argues that different 'circular' approaches centred upon the life cycle design phases can provide practical guiding strategies during the design process and thus promote sustainable design solutions for the circular economy within the United Nation's sustainable development goals.